Alloying and phase transformation in CdS/CdSe bilayers annealed with or without CdCl2. (1st March 2019) - Çiriş, A.; Başol, B.M.; Yılmaz, S.; Atasoy, Y.; Tomakin, M.; Küçükömeroğlu, T.; Bacaksız, E.
Abstract: The present paper studies the structural, compositional, morphological and optical properties of thin CdS/CdSe stacks annealed in an inert atmosphere or subjected to a CdCl2 treatment. The bilayer stacks were fabricated by chemical bath deposition (CBD) of a 50 nm thick CdS layer followed by evaporation of a CdSe film with equal thickness. It was found that when this stack was annealed at 400 °C for up to 10 min, no appreciable intermixing/alloying between the two layers was detected. Upon heating for 5–10 min in presence of a CdCl2 layerdisposed over the CdSe film, however, led to appreciable alloying and formation of CdSSe, which was confirmed through XRD, optical transmission and room temperature photoluminescence measurements. XRD data further showed thatthe CdS layer in the CdS/CdSe stack had nano-amorphous structure that did not change upon annealing in inert atmosphere. The CdSe layer of the stack, which had a cubic structure, also preserved its phase upon annealing in inert atmosphere. When the CdS/CdSe stack was CdCl2 treated, the phase of the CdSSe alloy formed was transformed to hexagonal. These observations may have consequences in applications where CdS/CdSe bilayers are formed within device structures and subjected to various types of heat treatments.